Home-grown school feeding: assessment of a pilot program in Nepal - Rachana Manandhar Shrestha; Pepijn Schreinemachers; Mamta Gurung Nyangmi; Manoj Sah; Judy Phuong; Shraddha Manandhar; Ray-Yu Yang (BMC, 2020)
Abstract Background The Nepal School Meals Program reached 600,000 schoolchildren in basic education in 2017 and plays a key role in the government's strategy to increase children's academic and nutritional outcomes. A large part of the program is implemented through cash transfers with schools responsible for the school meal delivery. Home-grown school feeding, an approach in which local communities are given greater control over the school meals program and part of the food is sourced locally, may strengthen local ownership and improve meal quality, but there is a lack of evidence for impact. Methods This study piloted home-grown school feeding in 30 schools reaching nearly 4000 children in Sindhupalchok and Bardiya districts in Nepal with the aim to assess operations and outcomes in comparison to the regular cash-based school meals program. The study used a one-time post evaluation with a mixed methods approach. Qualitative data were collected through 12 focus group discussions and 28 key informant interviews with government and school staff, parents, cooks, cooperative members, World Food Programme representatives and other stakeholders involved in the pilot program. The quantitative part applied a quasi-experimental design and used cross-sectional data collected from 1512 children in 30 pilot and 30 control schools. Results The quantitative data indicated that children in the pilot schools had a significantly higher provision of midday school meals (+ 19%; p < 0.01) and a higher school meal quality in terms of dietary diversity (+ 44%; p < 0.01) and nutritional content (e.g. a 21%-points higher consumption of vitamin A-rich fruit and vegetables; p < 0.01). The qualitative data identified key drivers of these positive outcomes as the use of standard meal options, capacity building of local stakeholders, strengthened community ownership and accountability mechanisms, and local food supply chains. Maintaining the observed gains would require a 20-33% increase in the current budget per school meal in addition to the cost of capacity building. Conclusions This study for Nepal shows that home-grown school feeding strengthened operations of the school meals program and led to a significantly higher meal provision and quality of school meals.